Particle physics : - Seiden, Abraham (Addison Wesley, 2004)
Abraham Seiden brings more than 40 years of teaching and research experience to this advanced introductory particle-physics text. Designed for advanced undergraduates and graduate students in physics, Particle Physics: A Comprehensive Introduction provides the most complete and up-to-date introduction available. The author focuses on the basic principles of particle physics, using recent research data to illustrate key concepts, and provides a wealth of step-by-step calculations to develop students' understanding of core principles.